Advancing the effective implementation of the one environmental system for mining through cooperative environmental governance - Mpinga, Shamila (Department of Private Law, 2020)
In 2014, the One Environmental System for mining came into effect. This legislative framework was introduced to streamline the environmental regulation of mining activities by consolidating such regulation in the National Environmental Management Act (NEMA). The most significant aspect of the regulatory framework, for purposes of this research, is the allocation of powers to the authorities responsible for implementing the One Environmental System. The authorities tasked with implementing the One Environmental System are the Department of Mineral Resources and Energy (DMRE), the Department of Environment, Forestry and Fisheries (DEFF) and the Department of Human Settlements, Water and Sanitation (DHWS). In the distribution of power, the DMRE is tasked with enforcing the regulatory framework in the minerals extraction industry. The DEFF sets the regulatory framework and is the appeal authority for decisions taken by the DMRE. Finally, the DHWS is responsible for regulating and enforcing the National Water Act. Although introducing the One Environmental System has improved the regulation of the environment in relation to mining, its regulation - and, more so, enforcement - has received more criticism than praise. Intragovernmental fragmentation has been cited as a cause of ineffective implementation of the regulatory framework. A lack of cooperation between the departments hampers the objective of streamlining the environmental regulation of mining. Therefore, it is imperative that the authorised departments cooperate with each other to achieve the effective implementation of the One Environmental System for mining. The aim of this dissertation is to suggest ways to foster cooperation between the DMRE, DEFF and DHWS to achieve the effective implementation of the One Environmental System. This goal is achieved by providing an analysis of the implementation efforts of the three departments. Since the analysis shows that intragovernmental fragmentation has hampered the effective implementation of the regulatory framework, this research provides recommendations to improve the implementation of the One Environmental System.